Primary Adrenal Lymphoma: Two Case Series From China - Zeng, Jinyang; Yan, Fangfang; Chen, Yulong; Zang, Li; Chen, Kang; Lyu, Zhaohui; Dou, Jingtao; Mu, Yiming; Lin, Mingzhu; Yang, Guoqing (Frontiers in Endocrinology, 2022)
Objective Primary adrenal lymphoma (PAL) is a rare form of adrenal mass. We summarize our experience in its clinical presentation, biochemical indexes, radiological features, pathological information, therapy regimens, and outcomes. Methods This was an institutional review board-approved retrospective review of medical records and surgical pathology specimens of patients with a diagnosis of PAL at the Chinese People’s Liberation Army General Hospital and the First Affiliate Hospital of Xiamen University between July 2007 and July 2017. Results Twenty-six patients were identified. The mean age at presentation was 60.84 ± 13.14 years with a male-to-female ratio of 2.25:1 (18:8). The most common presenting symptoms were loss of appetite (65%, 17/26), weight loss (62%, 16/26), abdominal pain (58%, 15/26), and fatigue (58%, 15/26). The levels of lactate dehydrogenase (75%, 15/20), β2-microglobulin (100%, 10/10), C-reactive protein (82%, 14/17), and ferritin (88%, 7/8) and the erythrocyte sedimentation rate (83%, 10/12) were elevated. Bilateral involvement was seen in 21 of 26 patients (81%); 12 of 19 evaluated patients with bilateral lesions (63%) were confirmed to have adrenal insufficiency. On computed tomography (CT), the mean tumor diameter was 7.31 ± 3.35 cm and the median Hounsfield density was 37.0 HU (range: 31.0–45.0 HU); 67% (10/15) and 27% (4/15) of lesions presented with mild and moderate enhancement after injection of contrast medium. 18F-fluorodeoxyglucose positron emission tomography (FDG PET)-CT revealed not only an adrenal tumor but also extra-adrenal lesions. Diffuse large B-cell lymphoma (DLBCL) was the most common phenotype (92%, 24/26). Ninety-two percent (24/26) of patients received chemotherapy while 8% (2/26) received unilateral adrenalectomy plus chemotherapy. The prognosis of PAL was poor, with a general survival time of 7.20 ± 5.18 months. Conclusion PAL is a rare disease. The clinical characteristics of PAL include loss of appetite and weight loss. Endocrine evaluation should be performed to determine whether patients have adrenal insufficiency, especially patients with bilateral lesions. FDG-PET appears to be more accurate than other imaging modalities in revealing extra-adrenal sites. Better therapy is required to improve the poor prognosis of PAL.